2019
DOI: 10.1177/1724600819883658
|View full text |Cite
|
Sign up to set email alerts
|

Serum 5-S-cysteinyl-dopa levels as a predictive marker for the efficacy of nivolumab in advanced malignant melanoma

Abstract: Purpose: With the recent developments in novel molecular targeted therapy such as immune-checkpoint blockades, serine/threonine-protein kinase B-Raf, and mitogen-activated protein kinase kinase inhibitors, the prognosis of advanced malignant melanoma has been improving. 5-S-cysteinyl-dopa (5-S-CD), a precursor of pheomelanin, has been previously revealed to be a useful biomarker for advanced-stage malignant melanoma, especially in patients with distant metastases. Here, we aimed to assess and compare the utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In contrast, the HPLC for measuring 5-S-CD and the LC-MS/MS for measuring 6H5MI2C have the disadvantages of being expensive and requiring specialized knowledge and skills to perform, limiting their application. We have previously reported that the serum 5-S-CD levels may be a better predictive marker of nivolumab treatment e cacy than LD in patients with advanced MM [15]. Taken together with the results of the present study, serum melanin metabolites, especially 6H5MI2C measured by LC-MS/MS, appear to have the potential to be good markers for MM.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, the HPLC for measuring 5-S-CD and the LC-MS/MS for measuring 6H5MI2C have the disadvantages of being expensive and requiring specialized knowledge and skills to perform, limiting their application. We have previously reported that the serum 5-S-CD levels may be a better predictive marker of nivolumab treatment e cacy than LD in patients with advanced MM [15]. Taken together with the results of the present study, serum melanin metabolites, especially 6H5MI2C measured by LC-MS/MS, appear to have the potential to be good markers for MM.…”
Section: Discussionsupporting
confidence: 80%
“…The prognosis of advanced melanoma has been improved. The study by Umemura et al compared the utility of serum 5SCD and LDH levels as markers for predicting the effects of Nivo in treating advanced melanoma, and showed that serum 5SCD levels have the potential to be an excellent predictive marker for the efficacy of Nivo therapy in patients with advanced melanoma [104]. In detail, analyzing 12 metastatic melanoma patients under Nivo therapy, they showed that serum 5SCD levels decreased in 2 of 3 patients having a partial response and increased 4 of 8 progressive cases.…”
Section: Usefulness Of 5scd In Monitoring Treatments For Melanomamentioning
confidence: 99%